1995
DOI: 10.1055/s-2007-973054
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Problems in High Level Swimmers - Impingement, Anterior Instability, Muscular Imbalance?

Abstract: The objective was to study prevalence and underlying pathology of "swimmer's shoulder". Twenty-two competitive swimmers of national "D-Kader" (elite development swimmers) were evaluated by means of questionnaire, clinical examination and isokinetic testing of external rotation and internal rotation. At the examination current interfering pain necessitating a cessation or reduction of practice was found in 5 (23%) athletes. At isokinetic testing 8 (36%) athletes complained of shoulder pain. Any history of pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
3
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(91 citation statements)
references
References 3 publications
(4 reference statements)
1
71
3
13
Order By: Relevance
“…As razões abordadas para ocorrência de tal lesão são relacionadas comumente ao excesso de repetições associados ao desequilíbrio de força muscular (12,13,19,25) . As lesões musculares também foram referidas de maneira significante e, segundo alguns autores (13,25) , estão associadas com o mesmo fator causal das tendinopatias, reiterando repetição e desequilíbrio muscular.…”
Section: Discussionunclassified
“…As razões abordadas para ocorrência de tal lesão são relacionadas comumente ao excesso de repetições associados ao desequilíbrio de força muscular (12,13,19,25) . As lesões musculares também foram referidas de maneira significante e, segundo alguns autores (13,25) , estão associadas com o mesmo fator causal das tendinopatias, reiterando repetição e desequilíbrio muscular.…”
Section: Discussionunclassified
“…Fatigue of rotator cuff associated with increased workload allows anterosuperior humeral head translation and secondary impingement of the subacromial structures (3). High Prevalence of shoulder overuse injuries is reported in swimming (4,5), tennis (6) and other overhead sports such as badminton (7) volleyball (8) and handball (9).…”
Section: Introductionmentioning
confidence: 99%
“…Overhead athletes and other 44 professionals that require use of the arm in a predominant overhead position are at a 45 high risk of developing associated shoulder pains and injuries. A number of studies 46 have reported high prevalence of shoulder pain and injury in swimmers [Lo et al,47 1990, Rupp et al, 1995, Su et al, 2004, tennis players [Cools et al, 2008], baseball 48 players [Hsu et al, 2009] and other overhead throwing athletes [Laudner et al, 2006, 49 Lo et al, 1990, Wilk et al, 2002. Shoulder impingement accounts for the majority of 50 the reported complaints [Michener et al, 2003].…”
mentioning
confidence: 99%